Time Trend Analysis of Ambient Air Quality and Increased ISPA in Kendari City - Hidayat, Muh. Taufik; Jayadipraja, Erwin Azizi; Asrullah, Muhammad; Astawa, Kadek Wiana (Miracle Journal of Public Health, 2024)
Acute Respiratory Infections (ARI) kill around 4 million people every year. Infants, children, and the elderly are most at risk. Each year, more than 2 million children under five years old die from ISPA. This research aims to describe the trend of ARI sufferers among toddlers in Kendari City for 2021-2023. The type and design of the research is descriptive. The population and sample (total sampling) are all toddlers suffering from ARI in Kendari City in 2021-2023, namely 23,508 toddlers. The research results show that the number of ARI cases in toddlers in Kendari City continues to increase every year. In 2021, it will be 24%; in 2022, it will be 36.2%; and in 2023, it will be 39.7%. During the 2021-2023 period, the number of male toddlers suffering from ARI was 52.7% greater than that of females, 47.2%. The number of ARI cases in the <1 year age group was 25.2%, and in the 1-<5 year age group was 74.7%. The health center with the highest number of ARI sufferers is the Puwatu Health Centre, with 15.5% of cases, and the lowest is the Jatiraya Health Centre, with 0.9% of cases. This research concludes that there is an increasing trend in the number of toddlers suffering from ARI in Kendari City for 2021-2023. Community health centers should provide education through posyandu activities regarding the dangers of ARI in toddlers and efforts to overcome them.